2019
DOI: 10.5194/nhess-19-2183-2019
|View full text |Cite
|
Sign up to set email alerts
|

Environmental controls on surf zone injuries on high-energy beaches

Abstract: Abstract. The two primary causes of surf zone injuries (SZIs) worldwide, including fatal drowning and severe spinal injuries, are rip currents (rips) and shore-break waves. SZIs also result from surfing and bodyboarding activity. In this paper we address the primary environmental controls on SZIs along the high-energy meso–macro-tidal surf beach coast of southwestern France. A total of 2523 SZIs recorded by lifeguards over 186 sample days during the summers of 2007, 2009 and 2015 were combined with measured an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 74 publications
8
29
0
Order By: Relevance
“…42 Here, the life-risk was found to systematically increase with the wave factor Wf, which is in line with Castelle et al, but contrast with Scott et al 43 in UK where hazard was maximised for just below average Wf. In a previous study, 44 it was qualitatively shown that the beach morphology, which has a profound impact on rip current hazard, was important to the number of drowning incidents. Given the low number of studied seasons and events, and the likely contrasting beachgoer profiles between seasons, it was not possible to robustly address the influence of the bathymetry.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…42 Here, the life-risk was found to systematically increase with the wave factor Wf, which is in line with Castelle et al, but contrast with Scott et al 43 in UK where hazard was maximised for just below average Wf. In a previous study, 44 it was qualitatively shown that the beach morphology, which has a profound impact on rip current hazard, was important to the number of drowning incidents. Given the low number of studied seasons and events, and the likely contrasting beachgoer profiles between seasons, it was not possible to robustly address the influence of the bathymetry.…”
Section: Discussionmentioning
confidence: 94%
“…Our models tend to overestimate the risk on days associated with moderate to high risks; some variables may thus be unknown, related to the beach morphology and the beach attendance. First, the summer beach morphology along the Gironde coast is very variable with rip channel exhibiting different morphologies from one summer to another, 44 and even in space with more gently sloping and less channelized beaches northwards. Given that, for instance, the relative depth of the rip channels is critical to rip current flow speed, 46 and thus physical hazard, and that beach type also influence attendance 47 consideration of a constant beach morphology is limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the highest peak is much earlier between 13h-15h compared to shore-break injuries. This might be explained by the fact that in summer more high tides with larger tidal ranges occur during late afternoon (Castelle et al, 2019). Temperature and insolation show comparable patterns to the shore-break BN with warm sunny days between 20-28 C°having the highest probability.…”
Section: Scenario Analysismentioning
confidence: 93%
“…The Gironde coast is located in southwest of France and stretches approximately 140 km from the La Salie Beach (La Teste) in the south to the Gironde Estuary in the north, and is interrupted by the Arcachon tidal inlet (Figure 1a). It is a meso-macrotidal environment with spring tidal range reaching 5 m. Wave conditions vary seasonally with a 99.5% exceedance significant wave height H s of 5.6 m, and occasional severe storms with H s > 8 m. Summers are associated with smaller waves with a mean H s of around 1.2 m and a dominant W-NW incidence (Castelle et al, 2019).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation